2022
DOI: 10.1021/acs.chemmater.2c00462
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Mass Transfer Barriers in Metal–Organic Frameworks

Abstract: Identifying mass transfer limitations is imperative for the practical application of nanoporous solids in adsorptive separations and catalysis. In particular, metal–organic frameworks (MOFs) with a staggering assortment of unique pore architectures and chemical binding sites are one class of materials where understanding structure–property relationships can facilitate material design. Here, we performed volumetric physisorption measurements and collected n-hexane adsorption isotherms of nine Zr-MOFs with uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…Thus, the interfacial resistance is essentially dependent on the fluid–solid interaction potential. In practice, the interfacial resistance is frequently represented in terms of a finite surface permeability used in a boundary condition for a diffusion model; , however, the use of such a boundary condition in finite systems has been questioned, as the entry length is not negligible in comparison to system size in such cases, and a model considering nonuniform transport coefficient considered more appropriate …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the interfacial resistance is essentially dependent on the fluid–solid interaction potential. In practice, the interfacial resistance is frequently represented in terms of a finite surface permeability used in a boundary condition for a diffusion model; , however, the use of such a boundary condition in finite systems has been questioned, as the entry length is not negligible in comparison to system size in such cases, and a model considering nonuniform transport coefficient considered more appropriate …”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, interfacial resistance to fluid transport in nanomaterials, as determined by fitting of diffusion models with finite surface permeability to transient uptake data, is believed to arise from surface pore blockages and structural distortions. 6,9−11 On the contrary, it has also been observed that the low surface permeability is largely nonstructural in origin, and not entirely due to blockages and surface defects, 12 and that it may be a surface diffusion process occurring in a finite region in the vicinity of the pore mouth or external surface. 13−15 In support, molecular dynamics (MD) simulations have suggested the existence of interfacial resistance even in ideal materials, albeit putatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These frameworks have one-dimensional channels that create a direct diffusional path, which simplified our analysis by eliminating the effect of tortuosity throughout multiple interconnected pathways. , Previous mass transport studies in MOFs have identified additional diffusional resistances at the surfaces of MOF particles, termed surface barriers. These features may result from structural defects on the particle surface, or the narrowing or blockage of pore mouths. , We sought to determine whether surface permeation or intracrystalline diffusion is rate limiting to overall mass transport, as well as quantify the mass transport coefficients of hydrocarbons into Co 2 Cl 2 BBTA and Co 2 Cl 2 BTDD. We used a recently reported volumetric method to measure the gas-phase diffusion of hydrocarbons in bulk MOF powders, which allowed us to quantify mass transport simultaneously while collecting adsorption isotherms.…”
Section: Introductionmentioning
confidence: 99%
“…The surface barrier phenomenon 22,23 is related to the steps A and B, while step C is usually the rate limiting factor. 6,24 As the permeation is directly proportional to the diffusivity and adsorbate solubility, managing the interpore diffusion is the key in case of nanoporous solids. Earlier studies revealed that the diffusion in the nanoporous solids, e.g.…”
Section: Introductionmentioning
confidence: 99%